2010
DOI: 10.1128/mmbr.00031-09
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Immunomodulatory Roles of Bacterial Outer Membrane Vesicles

Abstract: SUMMARY Outer membrane (OM) vesicles are ubiquitously produced by Gram-negative bacteria during all stages of bacterial growth. OM vesicles are naturally secreted by both pathogenic and nonpathogenic bacteria. Strong experimental evidence exists to categorize OM vesicle production as a type of Gram-negative bacterial virulence factor. A growing body of data demonstrates an association of active virulence factors and toxins with vesicles, suggesting that they play a role in pathogenesis. One o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
753
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 807 publications
(777 citation statements)
references
References 153 publications
(166 reference statements)
16
753
0
8
Order By: Relevance
“…For many decades the formation of EMVs in prokaryotes was solely focused on bacteria (Kuehn & Kesty 2005;Ellis & Kuehn 2010;Kulp & Kuehn 2010). In bacteria with double membranes (referred to as diderm bacteria) they are generally derived from the outer membrane (OM) which is distinct from the cytoplasmic membrane, and are referred to as OMVs (Kulp & Kuehn 2010).…”
Section: Emvs In Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…For many decades the formation of EMVs in prokaryotes was solely focused on bacteria (Kuehn & Kesty 2005;Ellis & Kuehn 2010;Kulp & Kuehn 2010). In bacteria with double membranes (referred to as diderm bacteria) they are generally derived from the outer membrane (OM) which is distinct from the cytoplasmic membrane, and are referred to as OMVs (Kulp & Kuehn 2010).…”
Section: Emvs In Bacteriamentioning
confidence: 99%
“…OMVs are potent virulence factors of pathogenic diderm bacteria. These vesicles contain toxins, DNA, immunomodulatory compounds, communication factors and adhesins, and have been associated with cytotoxicity, bacterial attachment, intercellular DNA transfer and invasion (Dorward et al 1989;Kuehn & Kesty 2005;Ellis & Kuehn 2010;Maldonado et al 2011;Brown et al 2014). Increased vesiculation has been linked to bacterial stress and may play a role in carrying away toxic compounds, phages or unfolded proteins after exposure to stressful conditions (McBroom & Kuehn 2007;Macdonald & Kuehn 2013).…”
Section: Emvs In Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that OMV act as vehicles for protein transfer and interact with the host immune system. [7][8][9] We have previously demonstrated that M. catarrhalis OMV contain β-lactamase, and that secreted OMV protect NTHi and S. pneumoniae from amoxicillin-induced killing. 10 In the present study we investigated whether OMV derived from β-lactam resistant NTHi carry β-lactamase, and if β-lactamasecontaining OMV from NTHi or M. catarrhalis protect GAS from amoxicillin.…”
Section: Introductionmentioning
confidence: 99%
“…Secreted vesicles allow bacteria to disperse bacterial products into the surrounding environment in a concentrated manner (10,11). Vesicle formation appears to be a conserved process among both pathogenic and nonpathogenic, Gram-negative bacteria, and the role of outer membrane vesicles in pathogenesis are of great interest.…”
mentioning
confidence: 99%